2010
DOI: 10.1016/j.brainres.2010.04.040
|View full text |Cite
|
Sign up to set email alerts
|

Working memory capacity is related to variations in the magnitude of an electrophysiological marker of recollection

Abstract: The links between the resources available for cognitive control and the ability to recover and maintain episodic content were investigated by contrasting an ERP index of recollection (the left-parietal ERP old/new effect) with a measure of working memory capacity (WMC). Participants were given the O-Span measure of WMC and completed a retrieval task in which they had to make responses on one key to previously studied words (targets) and responses on a second key to words that were presented at retrieval on eit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
24
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 49 publications
7
24
0
Order By: Relevance
“…One early suggestion was that this strategy would be adopted when target information was easy to retrieve and diagnostic by itself (Herron and Rugg, 2003b); however, Rosburg et al recently suggested that strategic retrieval depends more on the ease of non-target retrieval. Other studies have demonstrated that the similarity of sources is not, by itself, a trigger for using strategic retrieval (e.g., Evans et al, 2010;Wilding et al, 2005) and have shown a correlation between working memory capacity and the ability to engage in strategic recollection (Elward and Wilding, 2010). The results from the present study indicate that strategic recollection also occurs during source monitoring tasks.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…One early suggestion was that this strategy would be adopted when target information was easy to retrieve and diagnostic by itself (Herron and Rugg, 2003b); however, Rosburg et al recently suggested that strategic retrieval depends more on the ease of non-target retrieval. Other studies have demonstrated that the similarity of sources is not, by itself, a trigger for using strategic retrieval (e.g., Evans et al, 2010;Wilding et al, 2005) and have shown a correlation between working memory capacity and the ability to engage in strategic recollection (Elward and Wilding, 2010). The results from the present study indicate that strategic recollection also occurs during source monitoring tasks.…”
Section: Discussionsupporting
confidence: 57%
“…As a result, the parietal ERP differences observed during source monitoring (RM or ISM) are not due to the mere inclusion of self-relevant information in the memory trace (e.g., cognitive operations) because parietal ERP differences persisted in these ISM studies in which all sources (i.e., actions) contained self-relevant characteristics. Instead, these results raise the possibility that internal sources prompt strategic recollection, as indicated by parietal effect differences (e.g., Bergström et al, 2009aBergström et al, , 2009bBergström et al, , 2007Elward and Wilding, 2010;Evans et al, 2010), when it simplifies or otherwise aids the judgment.…”
Section: Erps and Internal Source Monitoring (Ism)mentioning
confidence: 81%
See 1 more Smart Citation
“…In particular, these authors point to common activations in both kinds of tasks in the prefrontal cortex, which are described as being common control and monitoring mechanisms. Rather than straying too far into this promising avenue for further research, we confine our comments to how working memory mechanisms may be used in the exclusion task, and draw largely on the arguments proposed by Wilding and colleagues (Elward and Wilding, 2010;Elward et al, 2013). One observation is that intact recollection is not necessary at all, should sufficient capacity and reserve exist in a short-term store.…”
Section: Materials and Proceduresmentioning
confidence: 99%
“…One recent development is the finding that the control component of recollection (i.e. as measured in exclusion tasks) draws heavily upon working memory resources (Elward & Wilding, 2010;Elward, Evans, & Wilding, 2013). Our view is that working memory resources would be necessary to hold in mind information at test and reflect metacognitively, or strategically upon it.…”
Section: Introductionmentioning
confidence: 99%